Immunization stress-related response – Redefining immunization anxiety-related reaction as an adverse event following immunization. Issue 14 (23rd March 2020) - Gold, Michael S.; MacDonald, Noni E.; McMurtry, C. Meghan; Balakrishnan, Madhava Ram; Heininger, Ulrich; Menning, Lisa; Benes, Oleg; Pless, Robert; Zuber, Patrick L.F.
Abstract: The Council for the International Organizations of Medical Sciences (CIOMS) and WHO working group on pharmacovigilance defines five cause specific AEFI which includes an immunization anxiety-related reaction. Historically this term has been used to describe a range of symptoms and signs that may arise after immunization that are related to "anxiety" about the immunization. However, the term "anxiety" does not adequately capture all the elements of this cause specific AEFI. In 2015, the Global Advisory Committee for Vaccine Safety convened an expert working group with the purpose of redefining, preventing and managing this particular AEFI. The term "Immunization Stress-Related Response" is proposed to replace the former terminology. We present a manual that redefines this AEFI and present a framework for prevention, diagnosis and management in both an individual and also when such events occur as clusters and affect multiple individuals. Since such mass events can result in cessation of immunization programmes and/or a loss of public confidence, a communication response is essential.